SaeR as a novel target for antivirulence therapy against Staphylococcus aureus - Peng Gao; Yuanxin Wei; Suying Hou; Pok-Man Lai; Han Liu; Sherlock Shing Chiu Tai; Victor Yat Man Tang; Pradeep Halebeedu Prakash; Kong-Hung Sze; Jonathan Hon Kwan Chen; Hongzhe Sun; Xuechen Li; et al. (Emerging Microbes and Infections)
Staphylococcus aureus is a major human pathogen responsible for a wide range of clinical infections. SaeRS is one of the two-component systems in S. aureus that modulate multiple virulence factors. Although SaeR is required for S. aureus to develop an infection, inhibitors have not been reported. Using an in vivo knockdown method, we demonstrated that SaeR is targetable for the discovery of antivirulence agent. HR3744 was discovered through a high-throughput screening utilizing a GFP-Lux dual reporter system driven by saeP1 promoter. The antivirulence efficacy of HR3744 was tested using Western blot, Quantitative Polymerase Chain Reaction, leucotoxicity, and haemolysis tests. In electrophoresis mobility shift assay, HR3744 inhibited SaeR-DNA probe binding. WaterLOGSY-NMR test showed HR3744 directly interacted with SaeR’s DNA-binding domain. When SaeR was deleted, HR3744 lost its antivirulence property, validating the target specificity. Virtual docking and mutagenesis were used to confirm the target’s specificity. When Glu159 was changed to Asn, the bacteria developed resistance to HR3744. A structure–activity relationship study revealed that a molecule with a slight modification did not inhibit SaeR, indicating the selectivity of HR3744. Interestingly, we found that SAV13, an analogue of HR3744, was four times more potent than HR3744 and demonstrated identical antivirulence properties and target specificity. In a mouse bacteraemia model, both HR3744 and SAV13 exhibited in vivo effectiveness. Collectively, we identified the first SaeR inhibitor, which exhibited in vitro and in vivo antivirulence properties, and proved that SaeR could be a novel target for developing antivirulence drugs against S. aureus infections.